2017
DOI: 10.1038/s41598-017-18207-y
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal to Stratify the Intermediate-Risk Thyroid Nodules According to the AACE/ACE/AME Guidelines with Ultrasound Features

Abstract: To propose a risk stratification system for intermediate-risk thyroid nodules (TNs) according to American Association of Clinical Endocrinologists, American College of Endocrinology and Associazione Medici Endocrinologi Medical (AACE/ACE/AME) Guideline with ultrasound (US) features. 1000 patients with 1000 nodules (902 benign nodules and 98 malignant nodules) were included. All the nodules were confirmed with either fine needle aspiration (FNA) cytology and follow-up or histology results after surgery. Univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In some cases, an approach that combines different ancillary techniques has proved to offer greater diagnostic accuracy than a single technique alone [ 18 , 36 39 ]. As reported in previous studies [ 15 17 , 40 ], our data confirmed the role of conventional ultrasound as the basis for the assessment, owing to its advantages in terms of cost and time. However, the need for a scoring system that performs better than the separate evaluation of single items is increasingly evident.…”
Section: Discussionsupporting
confidence: 90%
“…In some cases, an approach that combines different ancillary techniques has proved to offer greater diagnostic accuracy than a single technique alone [ 18 , 36 39 ]. As reported in previous studies [ 15 17 , 40 ], our data confirmed the role of conventional ultrasound as the basis for the assessment, owing to its advantages in terms of cost and time. However, the need for a scoring system that performs better than the separate evaluation of single items is increasingly evident.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have indicated that no single ultrasound feature can directly and accurately predict the malignancy of a nodule ( 36 , 37 ); however, some characteristics, such as hypoechogenicity, irregular margins, taller-than-wide shape, microcalcifications and solidity, may predict thyroid cancer ( 14 , 16 , 17 , 19 , 20 , 38 ). In this study, solidity, hypoechogenicity, irregular margins, taller-than-wide shape, microcalcifications and posterior echo attenuation associated with malignant nodules, whereas regular halo associated with benign nodules.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ultrasonography can guide FNA, which can reduce the generation of non-diagnostic specimens. Ultrasound features, such as solidity, hypoechogenicity, microcalcifications, taller-than-wide shape and irregular margins, are useful in the diagnosis of malignant nodules ( 13 , 14 , 15 , 16 , 17 , 18 ). Furthermore, other studies have reported that a simple cystic and spongiform appearance have a higher negative predictive value (NPV) for malignancy ( 13 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another promising system, developed by the British Thyroid Association (BTA), was introduced to the 2014 guidelines on the management of thyroid cancer. The recommendation aims to stratify thyroid nodules as benign, suspicious or malignant based on ultrasound appearances termed U1-U5 [25] . It considers the following US features as predictors of malignancy: Eccentric location of the solid portion in a partially cystic nodule, the nonsmooth margins, the hypo-echogenicity of the solid portion, micro-calcifications, and "Taller-thanwide" shape [24] .…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…These images are assumed to make it easier for more recognition of different morphological patterns and thus easier imaging practice. The system presents the morphological class with no numerical scoring system and size is not included in criteria [25] . These graphic references are supposed to encourage the sonographer to translate his findings into a particular degree of concern, thus allowing for a common "Thyroid language" among health care professionals to communicate ultrasound findings.…”
Section: List Of Abbreviationsmentioning
confidence: 99%